MODEL OF COLLABORATION BETWEEN SUPPLIER AND MANUFACTURER FOR THE PROFIT SUPPLY CHAIN - ROMENOR, MUHAMMAD RAFAEE (2012)
A WORLD CLASS SUPPLY CHAIN MANAGEMENT INVLOVES VALUE0ADDING ACTIVITIES IN THE SUPPLYING PROCESS WHICH TO DELIVER THE SUPPLYING SERVICE AT ITS OPTIMAL TOTAL COST, THE LEAST LEAD TIME AND AT THE HIGHEST QUALITY. THIS PROJECT WILL PRESENTS THE NEW MODEL WHICH SHALL DETERMINE THE OPTIMAL SOLUTION IN TERM OF MINIMUM PRESENT VALUE OF JOINT TOTAL COST CAN BE ACHIEVED UNDER CONSTRAINTS.